Can a Representative-Agent Model Represent a Heterogeneous-Agent Economy - AN, Sungbae (Institutional Knowledge at Singapore Management University, 2009)
Accounting for observed fluctuations in aggregate employment, consumption, and real wage using the optimality conditions of a representative household requires preferences that are incompatible with economic priors. In order to reconcile theory with data, we construct a model with heterogeneous agents whose decisions are difficult to aggregate because of incomplete capital markets and the indivisible nature of labor supply. If we were to explain the model-generated aggregate time series using decisions of a stand-in household, such a household must have a nonconcave or unstable utility as is often found with the aggregate US data.